Curvature-dependent shear bond strength of different attachment materials for orthodontic lingual indirect bonding - Jungbauer, Rebecca; Al-Burghol, Paul; Rosentritt, Martin; Kirschneck, Christian; Proff, Peter; Paulsen, Friedrich; Hammer, Christian (Scientific Reports, 2021)
To evaluate the shear bond strength (SBS) of different attachment materials used for lingual bonding, the influence of artificial aging and the radii of curvature of the enamel surface on SBS, 192 third molars were photographed to determine the radius of curvature of the oral surface. After phosphoric acid etching a cylindrical test piece was bonded to the oral enamel using a mold that was filled with a chemically curing (Maximum Cure, Transbond IDB Premix) or a dual-curing (Nexus NX3, RelyX Unicem2) attachment material. SBS was tested after 24 h, 500 thermal cycles or 90 days at 37 °C with a universal testing machine. Computed tomography scans were performed to determine the bonded surface and calculate SBS. Values ranged from 8.3 to 20.9 MPa. RelyX Unicem2 showed the highest SBS values at baseline, 500 thermal cycles and after 90 days (p < 0.001). Ninety days of wet storage significantly reduced SBS of Maximum Cure (p = 0.028). The radius of curvature correlated positively with SBS (rs = 0.204, p = 0.005). The SBS of all attachment materials was sufficient for clinical use, even after artificial aging. RelyX Unicem2 showed almost twice as high SBS values as the other attachment materials.
CRIS-Team Scopus Importer:2021-08-27